Dinamika Interaksi Auditor Manajemen dalam Pemanfaatan Informasi Akuntansi untuk Pengendalian Strategis Persediaan - Dandi Aprila; Lidya Primta Surbakti; Ali Tafriji Biswan (Universitas Negeri Padang, 2026)
Although inventory control and audit practices have received increasing attention in prior studies, research specifically examining how auditor–management interactions influence the strategic use of accounting information remains limited. This study explores how communication dynamics, interpretation processes, and organizational practices shape the utilization of audit information for strategic inventory control in a manufacturing company. A qualitative case study approach was employed involving eight participants selected through purposive sampling, consisting of internal auditors, warehouse personnel, and operational managers. Data were collected through in-depth interviews, observations during stock opname, and document analysis, and were analyzed using thematic analysis following the Miles–Huberman framework. The findings reveal that recurring inventory discrepancies stem not only from technical shortcomings but also from interpretive gaps between auditors and management, limited cross-functional dialogue, and the absence of mechanisms that elevate audit information to the strategic level. As a result, audit functions primarily as a diagnostic control rather than an interactive control, causing its insights to remain confined to operational correction instead of informing strategic decisions. The study contributes to the literature on strategic management accounting and audit-as-a-social-process by demonstrating that the strategic value of audit information depends on shared interpretation and interactive communication. It concludes that strengthening cross-functional dialogue, improving information integration, and fostering an open information culture are essential for enhancing the strategic role of audits. The study also offers avenues for future research on cultural and structural factors influencing the integration of audit information into organizational strategy.